Knowledge, attitude and practices towards biomedical waste management among nursing students in UiTM Selangor Puncak Alam Campus / Rosuzeita Fauzi, Siti Nur Firdanis Dahari, Nur Farah Syahira Sha'ari - Fauzi, Rosuzeita; Dahari, Siti Nur Firdanis; Sha'ari, Nur Farah Syahira (Faculty of Health Sciences, Universiti Teknologi MARA, 2019)
Biomedical waste means any waste, which is generated during the diagnosis, treatment or immunization of human beings or animals in a health institution. Incorrect and inappropriate knowledge of management of healthcare waste may contribute to serious health consequences and a significant impact on the environment as well. The aim of the study is to assess the level of knowledge, attitude and practices toward biomedical waste management among nursing students in UiTM Selangor Puncak Alam Campus. A cross-sectional study was performed on 157 nursing students from second, third and fourth-year students which were selected using purposive sampling. The instruments used in this study was questionnaires on Knowledge, Attitude, and Practices of Biomedical Waste Management to assess knowledge, attitude and practices (KAP) of BMW management among nursing students. The mean scores of KAP were M= 6.75, SD= 1.25, M= 15.07, SD= 2.54 and M= 7.25, SD= 1.28. There is a significant difference (p= 0.001) between the level of education and attitude. Nursing students have good knowledge, positive attitude and good practices. Besides, diploma students had a better attitude than degree students.